Leech's Politeness Maxims in Indonesian Digital Communication: Enactment, Violation, and Negotiation on X and Instagram - Radi Sukma; Nguman Abdul Manaf; Tressyalina (SUJANA: Education and Learning Review, 2025)
The transformation of communication in the digital era has created new challenges for the application of conventional politeness norms, particularly in non-Western social media contexts that remain underrepresented in international pragmatics scholarship. This study examines how Indonesian netizens enact, violate, and negotiate Leech’s six politeness maxims across 150 public comments collected from X and Instagram between January and February 2025. Employing a descriptive qualitative approach with contextual pragmatic analysis, the study classifies each comment against Leech’s tact, generosity, approbation, modesty, agreement, and sympathy maxims. Inter-coder reliability was established through independent coding by two researchers, yielding a Cohen’s kappa coefficient of κ = 0.81. Results indicate that the approbation, tact, and sympathy maxims are most consistently applied, reflecting Indonesian cultural orientations toward appreciation, face protection, and empathetic concern. The agreement and modesty maxims are most frequently violated, particularly in politically charged discourse, where categorical disagreement and epistemic self-assertion function as identity-expressive strategies. Five cross-cutting negotiation strategies were identified: contextual adaptation, linguistic mitigation, emoji-mediated modulation, indirect humor, and in-group versus out-group differentiation. These findings demonstrate that politeness in Indonesian digital communication has not eroded but transformed into a hybrid, contextually negotiated repertoire. The study contributes to digital pragmatics theory and provides an empirical foundation for developing communication ethics curricula in Indonesian language education.